2023
DOI: 10.3389/fpubh.2023.1079601
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed diseases: Needs and opportunities in 20 countries participating in the Undiagnosed Diseases Network International

Abstract: IntroductionRare diseases (RD) are a health priority worldwide, overall affecting hundreds of millions of people globally. Early and accurate diagnosis is essential to support clinical care but remains challenging in many countries, especially the low- and medium-income ones. Hence, undiagnosed RD (URD) account for a significant portion of the overall RD burden.MethodsIn October 2020, the Developing Nations Working Group of the Undiagnosed Diseases Network International (DNWG-UDNI) launched a survey among its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Nevertheless, access to broader genomics tests is limited in low- and middle-income countries, with absent or scarce availability and/or coverage for such testing. Overcoming these challenges is relevant for patients and families, and also for the healthcare systems in Chile and many countries, since testing performed locally is more likely to eventually have financial coverage than testing performed abroad ( Encina et al, 2019 ; Taruscio et al, 2023 ). Limited mid-throughput NGS equipment is available in several Latin American countries ( Torres et al, 2017 ) and increased during the COVID-19 pandemic for SARSCoV-2 diagnosis and surveillance ( Pan American Health Organization, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, access to broader genomics tests is limited in low- and middle-income countries, with absent or scarce availability and/or coverage for such testing. Overcoming these challenges is relevant for patients and families, and also for the healthcare systems in Chile and many countries, since testing performed locally is more likely to eventually have financial coverage than testing performed abroad ( Encina et al, 2019 ; Taruscio et al, 2023 ). Limited mid-throughput NGS equipment is available in several Latin American countries ( Torres et al, 2017 ) and increased during the COVID-19 pandemic for SARSCoV-2 diagnosis and surveillance ( Pan American Health Organization, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scarce information exists on molecular diagnosis of RTT in patients from Latin America, mostly due to limited availability and coverage of genomic testing ( Taruscio et al, 2023 ). Motivated by a request from the leadership of the local RTT patient organization in Chile and in collaboration with them, we developed this pilot study.…”
Section: Introductionmentioning
confidence: 99%
“…A systematized public health program and budget for sequencing large numbers of patients would expedite IEiM diagnoses, especially for those associated with more than one gene (i.e., PA, MSUD, or MMA) or without specific biomarkers for a biochemical diagnosis such as glycogen storage disease (GSD). As other authors have demonstrated, it is necessary to improve access to WES or WGS in this group of patients [ 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the pilot survey ( 3 ), this study was developed within the WG to further investigate the main needs for diagnosing undiagnosed patients, aiming to better characterize existing barriers, explore policy aspects, and correlate those needs to national healthcare economics and advocacy organizations.…”
Section: Methodsmentioning
confidence: 99%
“…To map unmet needs and opportunities, a first pilot survey was launched in October 2020 among the UDNI Developing Nations Working Group (UDNI DN WG, hereafter WG) ( 3 ). The WG is composed of representatives from 20 countries, including developed as well as low- and middle-income countries (LMIC).…”
Section: Introductionmentioning
confidence: 99%